Clinical outcomes of uterine sarcomas: results from 14 years worth of experience in the Kinki district in Japan (1990–2003). Issue 3 (1st April 2006) - Kokawa, K.; Nishiyama, K.; Ikeuchi, M.; Ihara, Y.; Akamatsu, N.; Enomoto, T.; Ishiko, O.; Motoyama, S.; Fujii, S.; Umesaki, N.
Abstract : To review clinical outcomes and therapeutic varieties, we were invited to submit data from the patients who were treated for uterine sarcomas in Japan from 1990 to 2003. Uterine sarcomas were defined as leiomyosarcoma (LMS), endometrial stromal sarcoma (ESS), and carcinosarcoma (CS). Of a total of 97 patients, 36 (37.1%) were diagnosed with LMS of the uterine corpus, 15 (15.5%) with ESS, 46 (47.4%) with CS. Median age at diagnosis was 59 (21–85) years. Clinical stages based on FIGO were 41 (42.3%) with stage I disease, 6 (6.2%) with staged II, 34 (35.1%) with stage III, and 16 (16.5%) with stage IV. The median follow-up period for all patients was 13 (1–108) months and median disease-free period was 9 (0–96) months. The 1-year survival rate and disease-free survival (DFS) rate were calculated in patients with all sarcomas (overall survival [OAS], 61.3%; DFS, 46.6%). Statistical analysis showed that younger age (less than 50 years), early stage (stages I and II), and surgical procedure (extended hysterectomy [EH] and radical hysterectomy [RH]) were associated with significantly better OAS. Histologic types did not affect the survival period. In conclusion, aggressive surgery including EH or RH at the time of initial operation offers the possibility of prolonged survival.